Tesco plc. A company to invest in? - Huynh, Luan (2006)
The exciting world of finance has given many people, ranging from individual investors to academic researchers, incentives to explore the ways to receive financial rewards with certainty. After many decades, however, the debate of whether the market is efficient or whether stock prices are predictable still continues. Many people have made their piece with the concept of market efficiency, which suggests that there are no opportunities to gain abnormal profits from financial markets. Others continue to question past results and propose new solutions. Even results obtained through painful observations of large volumes of stocks over an extensive period of time and the use of statistical tools have been subject to criticism. Therefore, it does not make sense to attempt a test of market efficiency for a dissertation of this size and with such limited time and resources available. Instead, a logical and simpler approach is used. It is argued that there are clear signs which do indicate the potential for the future success of a company, and hence there are higher chances for the appreciation of such a company's stock prices. The claim is being made that investing in these growth stocks will give a higher chance of capital gains or better prospects for stable income in form of dividends for any investor. A company that seems to provide rewarding prospects for investors is Tesco plc. The results of the qualitative research approach which has been chosen as the main research technique for this dissertation supports the claim that Tesco would be a good choice for future capital gains as well as for stable income through generous dividends payouts.